Improving quality through clinical registries in urology. Issue 4 (July 2017) - Tyson, Mark D.; Barocas, Daniel A.
Abstract : Purpose of review: In this review, we highlight the use of clinical registries for quality improvement and research purposes in urology. We focus on national and regional clinical database registries, such as the National Surgical Quality Improvement Programme, the Cancer of the Prostate Strategic Urologic Research Endeavor, the Michigan Urological Surgery Improvement collaborative and the American Urological Association Quality Registry programme. Recent findings: It is widely known that claims-based and institutional databases are limited in their capacity to provide granular, real-time data for quality improvement purposes. As a result, clinical registries have emerged as an attractive alternative given their ability to capture large amounts of data across networks of health records. Another added benefit of Federally Qualified Clinical Data Registries (QCDRs) is the ability to meet emerging Medicare quality reporting standards, such as Physician Quality Reporting System and Meaningful Use. Despite the enthusiasm for QCDRs in the field of urology, however, myriad challenges remain in their implementation and widespread adoption including integration of existing health-information technology infrastructure, the accurate measurement of quality measures and the availability of clinically relevant quality measures in subspecialty practices. Summary: Quality measurement and improvement have become important aspects of modern clinical practice. Advances in health information technology have ushered in new tools, such as clinical registries, which simultaneously improve the quality of scientific research and clinical care while assisting eligible professionals in meeting federally mandated reporting requirements.